Bulk band inversion and surface Dirac cones in LaSb and LaBi: Prediction of a new topological heterostructure - Urmimala Dey (Nature Portfolio, 2018)
Abstract We perform ab initio investigations of the bulk and surface band structures of LaSb and LaBi and resolve the existing disagreements about the topological property of LaSb, considering LaBi as a reference. We examine the bulk band structure for band inversion, along with the stability of surface Dirac cones (if any) to time-reversal-preserving perturbations, as a strong diagnostic test for determining the topological character of LaSb, LaBi and LaSb-LaBi multilayer. A detailed ab initio investigation of a multilayer consisting of alternating unit cells of LaSb and LaBi shows the presence of band inversion in the bulk and a massless Dirac cone on the (001) surface, which remains stable under the influence of time-reversal-preserving perturbations, thus confirming the topologically non-trivial nature of the multilayer in which the electronic properties can be tailored as per requirement. A detailed $${{\mathbb{Z}}}_{2}$$ Z2 invariant calculation is performed to arrive at a holistic conclusion.